2016
DOI: 10.3171/2015.9.spine15705
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar paraspinal muscle morphometry and its correlations with demographic and radiological factors in adult isthmic spondylolisthesis: a retrospective review of 120 surgically managed cases

Abstract: OBJECTIVE The objective of this study was to assess the cross-sectional areas (CSAs) of lumbar paraspinal muscles in adults with isthmic spondylolisthesis (IS), to compare them with those in the normative population, and to evaluate their correlations with demographic factors and MRI changes in various spinal elements. METHODS The authors conducted a retrospective study of patients who had undergone post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…Most demonstrated a decrease in the CT-evaluated muscle density [5, 10, 37, 38] and the CSA of the multifidus and erector spinae [3941]. On the other hand, US studies [19, 42] showed no association between the size of the multifidus and age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most demonstrated a decrease in the CT-evaluated muscle density [5, 10, 37, 38] and the CSA of the multifidus and erector spinae [3941]. On the other hand, US studies [19, 42] showed no association between the size of the multifidus and age.…”
Section: Resultsmentioning
confidence: 99%
“…Another MRI study from India [41] assessed the CSA of the lumbar paraspinal muscles in 120 adults with isthmic spondylolisthesis. Compared with normal controls, the mean CSA value for the erector spinae was significantly higher in the study cohort ( p = 0.002), whereas the CSA for the multifidus muscle was significantly lower ( p = 0.009).…”
Section: Resultsmentioning
confidence: 99%
“…In studies by Dohzono and Deng, it was suggested that paraspinal muscle was composed of multifidus and erector spinae [19,20]. In other studies, multifidus and erector spinae combined with either psoas muscle [27], quadratus lumborum [17], or psoas muscle/quadratus lumborum [15,25,26] were defined as paraspinal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…While PMA has been associated with ipsilateral LBP and radiculopathy, a study by Ploumis et al 30 found no correlation with duration and the severity of pain as measured by ODI and VAS. Interestingly, a study of 120 patients with surgically managed isthmic spondylolisthesis in which an association was found between the pathology and multifidus atrophy did not illustrate a similar association between multifidus atrophy and disc degeneration or facet arthropathy, 26 nor did it note significant reductions in psoas cross-sectional area to vertebral body area ratios (0.61 + 0.19, 0.63 + 0.20, P ¼ .427) in isthmic spondylolisthesis versus controls. In fact, the erector spinae cross-sectional area to vertebral body area ratio was increased (0.99 + 0.26, 0.89 + 0.24, P ¼ .002) in the isthmic spondylolisthesis group, suggesting compensatory hypertrophy.…”
Section: Choi Et Al 2016 Retrospective Cohortmentioning
confidence: 97%
“…25 Decreased multifidus cross-sectional area relative to vertebral body area was noted in a group of 120 individuals with isthmic spondylolisthesis when compared with normal controls (0.42 + 0.09, 0.46 + 0.14, P ¼.009). 26 The remaining studies implicating paraspinal muscle atrophy in thoracolumbar pathology development address Individuals with greater preoperative paraspinal muscle fat infiltration did not have significantly different failure rates than those with less degeneration after surgical decompression for symptomatic lumbar spinal stenosis.…”
Section: The Role Of Paraspinal Muscle Atrophy In Thoracolumbar Pathomentioning
confidence: 99%